Sublethal effects of Dayabon® on biological parameters of two-spotted spider mite, Tetranychus urticae (Koch) (Acari: Tetranychidae) - Mohammadreza Havasi; Katayoon Kheradmand; Elham Riahi (Journal of Crop Protection, 2020)
The two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae) is one of the most important pest species, with an extended range of host plants in the world. Use of chemical acaricides is one of the principle ways of controlling this pest. Considering the resistance to acaricides, as well as undesirable effects of chemical compounds, finding a suitable alternative way to control this pest is necessary. In this study sublethal effects of Dayabon®, a herbal extract, were investigated on some biological parameter of T. urticae at 2.140 g/l (LC5), 2.682 g/l (LC10) and 3.526 g/l (LC20). The estimated LC50 for T. urticae adult was 5.950 g/l. When adults were treated with LC10 and LC20 of Dayabon, the oviposition period was significantly reduced compared to LC5. The highest and the lowest fecundity (number of eggs laid per female) were 56.02 offspring/individual in control and 39.11 offspring/individual at LC20 respectively. In addition the net reproductive rate (R0) was decreased as concentration increased. Whereas, intrinsic rate of increase (r) and finite rate of increase (λ) were not affected by Dayabon. Considering the detrimental effects of Dayabon on some biological parameters of T. urticae, it can be concluded that this product can be used to develop targeted interventions aimed at integrated management of T. urticae.